Genome-wide association study and genetic mapping of BhWAX conferring mature fruit cuticular wax in wax gourd - Jinqiang Yan; Feng Chen; Piaoyun Sun; Wenrui Liu; Dasen Xie; Yulei Qian; Biao Jiang (BMC Plant Biology, 2022)
Abstract Background Wax gourd [Benincasa hispida (Thunb) Cogn. (2n = 2x = 24)] is an economically important vegetable crop of genus Benincasa in the Cucurbitaceae family. Fruit is the main consumption organ of wax gourd. The mature fruit cuticular wax (MFCW) is an important trait in breeding programs, which is also of evolutionary significance in wax gourd. However, the genetic architecture of this valuable trait remains unrevealed. Results In this study, genetic analysis revealed that the inheritance of MFCW was controlled by a single gene, with MFCW dominant over non-MFCW, and the gene was primarily named as BhWAX. Genome-wide association study (GWAS) highlighted a 1.1 Mb interval on chromosome 9 associated with MFCW in wax gourd germplasm resources. Traditional fine genetic mapping delimited BhWAX to a 0.5 Mb region containing 12 genes. Based on the gene annotation, expression analysis and co-segregation analysis, Bhi09G001428 that encodes a membrane bound O-acyltransferase (MBOAT) was proposed as the candidate gene for BhWAX. Moreover, it was demonstrated that the efficiency of a cleaved amplified polymorphic sequences (CAPS) marker in the determination of MFCW in wax gourd reached 80%. Conclusions In closing, the study identified the candidate gene controlling MFCW and provided an efficient molecular marker for the trait in wax gourd for the first time, which will not only be beneficial for functional validation of the gene and marker-assisted breeding of wax gourd, but also lay a foundation for analysis of its evolutionary meaning among cucurbits.